Closing the Gap Toward Zero Tetanus Infection for Voluntary Medical Male Circumcision: Seven Case Reports and a Review of the Literature - Galukande, Moses; Were, Leonard F.; Kigozi, Joanita; Kahendeke, Carol; Muganzi, Alex; Kambugu, Andrew (Surgical Infections, 2020)
Voluntary medical male circumcision (VMMC) is important for HIV prevention, providing up to 60% protection. Although VMMC is usually a safe procedure, it is not free of associated serious adverse events. In the Uganda VMMC program, which is available to males 10 years of age and older, 11 individuals were reported with tetanus infection out of almost 3.5 million circumcisions over an eight-year period (2009–2018). The majority had received tetanus vaccination prior to VMMC. Disproportionately and statistically significantly, the elastic collar compression method accounted for half the tetanus infection cases, despite contributing to only less than 10% of circumcisions done. This article describes gaps in presumed tetanus vaccination (TTV) protection along with relevant discussions and recommendations. Case Presentations: We present seven tetanus case reports and a review of the literature. We were guided by a pre-determined thematic approach, focusing on immune response to TTV in the context of common infections and infestations in a tropical environment that may impair immune response to TTV. It is apparent in the available literature that the following (mostly tropical neglected infections) sufficiently impair antibody response to TTV: human immunodefiency virus (HIV), pulmonary tuberculosis, nematode infections, and schistosomiasis. Conclusions: One of seven patients died (14% case fatality). Individuals with prior exposure to certain infection( s) may not mount adequate antibody response to TTV sufficient to protect against acquiring tetanus. Therefore, TTV may not confer absolute protection against tetanus infection in these individuals. More needs to be done to ensure everyone is fully protected against tetanus, especially in the regions where risk of tetanus is heightened. We need to characterize the high-risk individuals (poor responders to TTV) and design targeted protective measures.
Keywords: post-voluntary medical male circumcision; safe male circumcision; Uganda; wound care